2021
DOI: 10.1155/2021/9535061
|View full text |Cite
|
Sign up to set email alerts
|

Compound Taxus chinensis Capsule Combined with Chemotherapy for Non-Small-Cell Lung Cancer: A PRISMA-Compliant Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background. Compound Taxus chinensis capsule (CTCC), an antitumor Chinese patent medicine, has been commonly prescribed as an adjunctive agent to chemotherapy for the management of non-small-cell lung cancer (NSCLC); however, the effects of CTCC added to chemotherapy for NSCLC patients have never been comprehensively evaluated or summarized. Purpose. To assess the synergistic effects of CTCC and chemotherapy on NSCLC. Study Design. Evidence-based study, systematic review, and quantitative meta-analysis. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Recently, anti-PD-1 immunotherapy has caused more and more attention in the treatments of NSCLC [ 20 , 21 ]. In addition, combination therapy is a commonly used method for cancer treatment [ 22 ]. Thus, in this study, we observed the effect of the single application of C. sinensis as well as its combination therapy with PD-1inbihitor.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, anti-PD-1 immunotherapy has caused more and more attention in the treatments of NSCLC [ 20 , 21 ]. In addition, combination therapy is a commonly used method for cancer treatment [ 22 ]. Thus, in this study, we observed the effect of the single application of C. sinensis as well as its combination therapy with PD-1inbihitor.…”
Section: Introductionmentioning
confidence: 99%